2014
DOI: 10.1149/2.019401jss
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sonoluminescence Signal from Megasonic Irradiated Gas-Containing Aqueous Solutions Using Replaceable Single-Band Filters

Abstract: A simple method to resolve the features that are characteristic of hydroxyl radicals in sonoluminescence (SL) spectra from aqueous solutions has been developed. Using a modified version of cavitation threshold (CT) cell in which single band filters were sandwiched between the UV grade fused silica window and the photomultiplier tube (PMT) in the cell, photon emission in the wavelength range of 280 to 400 nm was measured. Four different single band filters, 280-305.5 nm, 300-340 nm, 335-375 nm and 374.5-397.5 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Immediately after preparation, MCLA containing solutions were transferred to a Cavitation Threshold (CT) cell for acoustic irradiation at ~ 0.93 MHz. A detailed description of the cell appears elsewhere [12]. Figure 1 shows a schematic of the modified CT cell set-up to enable simultaneous measurement of CL spectrum and photon emission.…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after preparation, MCLA containing solutions were transferred to a Cavitation Threshold (CT) cell for acoustic irradiation at ~ 0.93 MHz. A detailed description of the cell appears elsewhere [12]. Figure 1 shows a schematic of the modified CT cell set-up to enable simultaneous measurement of CL spectrum and photon emission.…”
Section: Methodsmentioning
confidence: 99%
“…While many studies on the characterization of hydroxyl and hydroperoxyl radicals have been reported [5][6][7], the detection and quantitation of hydrogen radicals formed in aqueous solution during sonication have not received much attention. In the detection of HO2• and H• radicals, their reaction with cupric (Cu 2+ ) ions has been recognized.…”
Section: Introductionmentioning
confidence: 99%